2011
DOI: 10.4137/jcm.s7399
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Obturator versus Sciatic Nerve Block in Addition to Continuous Femoral Nerve Block for Analgesia after Total Knee Arthroplasty

Abstract: Both obturator and sciatic nerve block in combination with femoral nerve block (FNB) have been suggested to be useful in relieving pain after total knee arthroplasty (TKA), compared with FNB alone. We compared their efficacy in this retrospective study. For six consecutive months, patients undergoing unilateral TKA under general anesthesia with continuous FNB plus obturator nerve block (n = 8) or continuous FNB plus sciatic nerve block (n = 8) were investigated. Knee pain was assessed using visual analogue sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…11 Thus, an equally divided sample of 50 was deemed sufficient for detection of a 50% reduction in morphine usage, with a 2-sided type 1 error of 5% and a power of at least 80%. A target sample size of 60 was established to increase the power.…”
Section: Discussionmentioning
confidence: 99%
“…11 Thus, an equally divided sample of 50 was deemed sufficient for detection of a 50% reduction in morphine usage, with a 2-sided type 1 error of 5% and a power of at least 80%. A target sample size of 60 was established to increase the power.…”
Section: Discussionmentioning
confidence: 99%
“…The total intravenous morphine consumption during the first 24 postoperative hours was 2 mg (interquartile range [IQR], 0-15) in the combined ONB and FTB group, 20 mg (IQR, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] in the FTB group (P = 0.0007), and 17 mg (IQR, in the LIA group (P = 0.002). The combined ONB and FTB group displayed reduced pain, nausea, and vomiting compared with the other groups.…”
mentioning
confidence: 99%
“…[5][6][7] Pain and opioid consumption after TKA apparently can be reduced by adding obturator nerve block (ONB) to an FNB. [8][9][10] The analgesic effect of ONB and FTB, as part of a multimodal analgesia regimen after TKA, has not been tested previously.…”
mentioning
confidence: 99%
“…However, combined femoral/tibial nerve anaesthesia helped to avoid peroneal nerve anaesthesia, which presents as paralysis of the muscles of the anterior shin compartment and foot drop. A Japanese study [29] found no statistically significant differences in post-operative pain intensity and morphine consumption following combined femoral/sciatic vs. femoral/obturator nerve anaesthesia. However, that study involved smaller groups (8 patients in each).…”
Section: Discussionmentioning
confidence: 97%